Short‐term variations in gene flow related to cyclic density fluctuations in the common vole. Issue 13 (July 2014) - Gauffre, Bertrand; Berthier, Karine; Inchausti, Pablo; Chaval, Yannick; Bretagnolle, Vincent; Cosson, Jean‐François
Abstract In highly fluctuating populations with complex social systems, genetic patterns are likely to vary in space and time due to demographic and behavioural processes. Cyclic rodents are extreme examples of demographically instable populations that often exhibit strong social organization. In such populations, kin structure and spacing behaviour may vary with density fluctuations and impact both the composition and spatial structure of genetic diversity. In this study, we analysed the multiannual genetic structure of a cyclic rodent, Microtus arvalis, using a sample of 875 individuals trapped over three complete cycles (from 1999 to 2007) and genotyped at 10 microsatellite loci. We tested the predictions that genetic diversity and gene flow intensity vary with density fluctuations. We found evidences for both spatial scale‐dependant variations in genetic diversity and higher gene flow during high density. Moreover, investigation of sex‐specific relatedness patterns revealed that, although dispersal is biased toward males in this species, distances moved by both sexes were lengthened during high density. Altogether, these results suggest that an increase in migration with density allows to restore the local loss of genetic diversity occurring during low density. We then postulate that this change in migration results from local competition, which enhances female colonization of empty spaces and male dispersal among colonies.